MYOPATHY AS A SIDE EFFECT OF STATIN THERAPY: MECHANISMS OF DEVELOPMENT AND PROSPECTS FOR TREATMENT - O. M. Drapkina; E. M. Chernova (Столичная издательская компания, 2015)
Statins are lipid-lowering drugs with proven efficacy that reduce cardiovascular risk and are well tolerated by most patients. Myopathy as a side effect of statin therapy is one of the most common reasons for their withdrawal. Its severity can range from asymptomatic increase of serum CPK to life-threatening rhabdomyolysis. Therefore it is necessary to remember about the possibility of its occurrence. The exact molecular mechanisms of muscle damage by statins are still unknown. Various hypotheses are suggested in this respect: fatty acid oxidation disorders, mitochondrial dysfunction, increased protein degradation in myocytes due to changes in atrogin-1 and ubiquitin activity, activation of autoimmune processes, intracellular depletion of essential metabolites, destabilization of cell membranes, impaired expression of genes involved in apoptosis and protein degradation. The theory that the reduction of intramuscular CoQ10 level is the cause of myopathy prevails. Additional intake of CoQ10 seems promising, but is not evidence-based.